KETERAMPILAN GURU DALAM PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL TERHADAP PEMBELAJARAN TEMATIK - Hakiki Hakiki; Hery Kresnadi; Asmayani Salimi (Universitas Tanjungpura, 2022)
KELAS IV, This study aims to find out how the skills of teachers in using digital learning media during the covid-19 period on thematic learning at SDN 03 Pontianak City. This research is a qualitative research in which the research was conducted by conducting interviews with the homeroom teacher of class IVA at SDN 03 Pontianak City. Procedures for collecting data by means of interviews and documentation. The data that has been collected is then processed and analyzed by means of data reduction, namely summarizing, selecting the main things, focusing on the important things, looking for themes and patterns. In the implementation process, the researcher reduced the data from the interview results from the informants, then selected important things to be used as data related to the research. After that, the researcher presented the data and finally drew conclusions. Based on the results of the research that has been carried out, it shows that the skills of teachers in using digital learning media are very good, varied, interesting, and innovative by the teachers. smartphones and laptops as well as applications that support digital learning media, namely WhatsApp, Youtube, and Google Meet.